2023
DOI: 10.1007/s11259-023-10178-y
|View full text |Cite
|
Sign up to set email alerts
|

Single layer centrifugation as a method for bacterial reduction in bull semen for assisted reproduction

Abstract: Semen samples contain bacteria originating from the animal urogenital tract, environment, and/or contamination during semen processing, negatively affecting sperm quality by producing toxins and/or competing for nutrients in extenders. The aims of this study were to evaluate two methods of Single-layer centrifuges (SLC), high and low density colloid, as a method for bacterial removal from bull semen, and to evaluate sperm quality after treatment. In total, semen samples from 20 bulls (3 ejaculates per bull) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Bacterial diversity might be connected to other factors not mentioned here. In a recent study on the microbial load in bull semen, the length of abstinence between collections (varying from one to three days) was found to influence seminal bacterial load, with the lowest levels in the ejaculates collected after one day´s abstinence (Cojkic et al 2023 ). Unfortunately, information on the frequency of semen collection is lacking for the stallions in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial diversity might be connected to other factors not mentioned here. In a recent study on the microbial load in bull semen, the length of abstinence between collections (varying from one to three days) was found to influence seminal bacterial load, with the lowest levels in the ejaculates collected after one day´s abstinence (Cojkic et al 2023 ). Unfortunately, information on the frequency of semen collection is lacking for the stallions in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in Staphylococcus vitulinus occurred in May, which was attributed to environmental factors, bedding quality changes, or increased staff workload during the breeding season. A recent study on bull semen microbial load found abstinence length (1-3 days) affected bacterial loads, with the lowest load being seen when semen collections were made daily (Cojkic et al 2023). This finding indicates the need to explore bedding, husbandry, and management effects on stallion semen microbial load to reduce antibiotic use in extenders.…”
Section: Bacterial Diversity In Stallion Semenmentioning
confidence: 99%